Insights into the structure and function of the hippocampus: implications for the pathophysiology and treatment of autism spectrum disorder - Long, Junzi; Li, Hui; Liu, Ying; Liao, Xingxing; Tang, Zhiqing; Han, Kaiyue; Chen, Jiarou; Zhang, Hao (Frontiers in Psychiatry, 2024)
The hippocampus is one of the brain areas affected by autism spectrum disorder (ASD).Individuals with ASD typically have impairments in hippocampus-dependent learning, memory, language ability, emotional regulation, and cognitive map creation. However, the pathological changes in the hippocampus that result in these cognitive deficits in ASD are not yet fully understood.In the present review, we will first summarize the hippocampal involvement in individuals with ASD.We will then provided an overview of hippocampal structural and functional abnormalities in genetic, environment-induced, and idiopathic animal models of ASD. Finally, we will discuss some pharmacological and non-pharmacological interventions that show positive impacts on the structure and function of the hippocampus in animal models of ASD. A further comprehension of hippocampal aberrations in ASD might elucidate their influence on the manifestation of this developmental disorder and provide clues for forthcoming diagnostic and therapeutic innovation.